Routes for Roots: A Mapping Shorthand Symbolism with Reference to Nelson Goodman's Hidden Ars Combinatoria. Issue 3 (3rd July 2017) - Moshammer, Gerald
Abstract : A shorthand symbolism for the relational mapping of categories (MSS) is introduced and developed on the basis of Nelson Goodman's structural methodology. Through a reconstruction of extensional isomorphism that Goodman introduces as a criterion for definitional accuracy, and a brief reminder of the argument structure behind his 'new riddle of induction', Goodman's radical ontological relativism is turned into a protological principle of what I call 'domain constituting philosophy'. MSS is demonstrated with reference to Goodman's symbol theory, particularly his notion of exemplification, as well as in a final structured comparison of Frege's 'sense' with Goodman's straightforward construction of 'secondary extension'.